2017
DOI: 10.2147/dddt.s144652
|View full text |Cite
|
Sign up to set email alerts
|

A novel transdermal nanoethosomal gel of betahistine dihydrochloride for weight gain control: in-vitro and in-vivo characterization

Abstract: BackgroundBetahistine dihydrochloride (BDH) is a histamine analog used to control weight gain, with short elimination half-life and gastric irritation as side effects.ObjectiveThe aim of the current investigation is to formulate and optimize a topical BDH ethosomal gel for weight gain control.Materials and methodsBox–Behnken design was applied to study the effect of independent variables: phosphatidylcholine (PC), propylene glycol (PG), and ethanol on vesicle size; entrapment efficiency; % drug release; and fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 48 publications
(59 reference statements)
1
15
0
Order By: Relevance
“…The in vitro release of SV-loaded nanospanlastics was implemented using the membrane diffusion technique using a glass cylinder which is attached to the USP dissolution apparatus shaft (USP apparatus II, Erweka DT-720, Germany) [ 20 , 25 ]. Firstly, the semi-permeable cellulose membrane was hydrated using phosphate buffer (pH = 7.4) for 24 h at room temperature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The in vitro release of SV-loaded nanospanlastics was implemented using the membrane diffusion technique using a glass cylinder which is attached to the USP dissolution apparatus shaft (USP apparatus II, Erweka DT-720, Germany) [ 20 , 25 ]. Firstly, the semi-permeable cellulose membrane was hydrated using phosphate buffer (pH = 7.4) for 24 h at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…The comparative ex vivo permeation study of the optimized SV-loaded SNVs was done using the membrane diffusion technique previously described except for the use of the pre-soaked rat skin instead of the dialysis membrane [ 20 , 25 ]. The pre-soaked rat skin was mounted carefully at the cylinder base with the SC side facing the donor chamber.…”
Section: Methodsmentioning
confidence: 99%
“…The ethosomal particle size increased with increasing the concentration of PC Phospholipids are the main component of the ethosomal wall and therefore expected to increase wall thickness and therefore increase particle size. 45 It is worth noting that propylene glycol and ethanol concentration had an antagonistic effect on the mean ethosomes' size; 46,47 this can be interpreted to the negative charge gained by both ethanol and PG, which causes electrostatic repulsion and prevention of vesicle aggregation. 48 Furthermore, the reduction in membrane thickness resulted from the interaction of ethanol and PG with the lipid bilayer.…”
Section: The Particle Size Of Ethosomal Rp Formulationsmentioning
confidence: 99%
“…The in vitro release study of Curcumin-loaded proniosomes was demonstrated by the dialysis method using a glass cylinder which is attached to the dissolution apparatus shaft (USP apparatus II, Erweka DT-720, Kreuzau, Germany) [17,35,36]. Initially, the semi-permeable cellulose membrane was hydrated using a phosphate buffer solution of pH = 7.4 [10] at 25 • C for 24 h. To maintain the sink condition, 0.5% (w/v) SLS was added to phosphate buffer, pH = 7.4, and used as the dissolution medium [37].…”
Section: In Vitro Release Study Of Curcumin-loaded Proniosomesmentioning
confidence: 99%